O efeito rescisório do recurso de revista e o seu cabimento para que o tribunal superior do trabalho atenda sua função de instância extraordinária com base nos princípios constitucionais do processo - Monteiro, Carlos Augusto Marcondes de Oliveira (2015)
This works derives from the certainty that judicial reviews are the main cause for the delays in lawsuits, specially at the Labor Courts, in which the plaintiff or the defendant are sometimes forced to waive their rights due to such lawsuits delays. It shall discuss alternatives, in the Extraodinary Review Procedure to adjust it to the constitutional procedural principles, since in practical terms one can verify 3 judicials instances, while we maintain that the Superior Labor Court should be restricted to its role as an extraordinary instance. This is not possible when one can not distinguish the effects of an Ordinary Review from that of the Extraordinary Review. The Extraordinary Review is subject to the competence of the panels of the Superior Labor Court and applicable to review the rulings of the Regional Labor Courts on Ondinary Reviews of individual claims whenever the requirements of CLT's article 896 are present. The limitation of the applicability of the Extraordinary Review is not enough to grant TST the status of a true Extraordinary Review Court. The scope of this work is to establish the exact function of the Superior Labor Court and its efectiveness, based upon the constitutional procedural principles, specially the due process of the law and the reasonable procedural length, which comprises the effectiveness and fast-track of the procedure by analysing the effects of both Ordinary and Extraordinary Reviews